Students’ subjective well-being, school bullying, and belonging during the COVID-19 pandemic: Comparison between PISA 2018 and PISA 2022 - Jian Li; Eryong Xue; Wenrui Zhou; Shuxuan Guo; Yimei Zheng (Humanities & Social Sciences Communications)
Abstract It is acknowledged that there are close relations among students’ subjective well-being, school bullying, and belonging. However, it is a dearth of exploring students’ subjective well-being, school bullying, and belonging during the COVID-19 pandemic using a large-scale data with comparative perspectives. Thus, this study used Program for International Student Assessment (PISA) 2018 and 2022 data to explore the factors that influenced students’ subjective well-being (SWB) in six countries and regions (the United Arab Emirates, Ireland, Panama, Mexico, Spain, and Hong Kong, China) and examine changes in these factors from 2018 to 2022. 153,052 students were assessed in 2018 and 2022, of which 78,257 were assessed in 2018 and 74,795 were assessed in 2022. The results showed that students’ SWB was significantly lower in 2022 than in 2018. Individual factors had the greatest influence on students’ SWB, and this influence increased from 2018 to 2022. The influence of family factors also increased during this period, whereas the influence of school factors decreased. The factor that was most closely related to SWB changed from parent-child relationships (2018) to students’ health level (2022), which significantly predicted students’ SWB. School bullying had a significant negative impact on students’ SWB, and the need to repeat the grade had a weak negative impact on SWB. In addition, school belonging played a mediating role in the relationship between bullying and students’ SWB, and the influence of students’ family economic status on their SWB was moderated by students’ peer relationships, teacher-student relationships, and parent-child relationships. This study also contributes to timely and effective educational and psychological interventions and implications for students’ subjective well-being, school bullying, and belonging under similar public health emergencies globally.